Co-inoculation of Rhizobium sp and Rhizobacteria for growth promotion of mungbean (Vigna radiata L.) - Qureshi, Muhammad Amjad; Ali, Abid; Ali, M. Asif; Ehsan, Shabana; Javed, Hina; Rafique, Munazza; Ijaz, Fraza; Mujeeb, Fakhar; Shehzad, Armghan; Niaz, Abid (Journal of Pure and Applied Agriculture, 2023)
Legume inoculation has been carried out to favour nitrogen fixation before the onset of green revolution. Rhizobium species have outstanding ability to colonize roots of legumes to promote nitrogen fixation and ultimately yields of legumes. Isolates of Rhizobium sp and Rhizobacteria (five of each type) have been characterized for the biosynthesis of IAA, P-solubilization, exopolysaccharide, siderophore production and other biochemical tests. Isolates showed higher values of IAA equivalents, solubilization index, siderophore unit and on the basis of other biochemical tests were selected for enhancing nodulation, growth parameters of mung bean in a field study at graded N levels i.e., 12 and 25 kg ha-1. Results clearly demonstrated the effect of bacterial inoculation at both N levels as compared to uninoculated ones. Co-inoculation effect on yield and nodulation parameters was significantly higher the separate application of isolates. Co-inoculation improved the grain and biomass yield of mung bean i.e., 984 and 2049 kg ha-1, respectively. Co-inoculation also enhanced nodule number and mass (45 and 0.080 g plant-1) as compared to the rest of inoculation levels and control at 25 kg N ha-1. Similarly, co-inoculation also enhanced the grain and plant NP content in comparison to remaining treatments. Moreover, soil analysis at harvest also showed higher soil N and available P i.e., 0.053% and 10.15 mg kg-1, respectively at higher N level. This field study suggested that interactive effect of symbiont and rhizobacteria could be used after thorough screening and valuable approach as compared to their individual application. However, there should be comprehensive strategy to use free living microbes in combination with their symbionts to promote quality foods and efficient nitrogen utilization in agricultural systems and exploring the hidden potential of rhizobacteria in field studies.